Strength Prediction Model of a Particle-Reinforced Shellproof Ceramic Composite - Ni, X.H.; Chen, C.; Liu, X.Q.; Zhang, S.Q. (Проблемы прочности, 2014)
On the basis of the microstructure of particle-reinforced shellproof ceramic composite, and the intergranular fracture feature, a dislocation pile-up fracture model of the small-particle ceramic composite is developed, the mechanism of formation, growth and coalescence of microcracks. The complex effect of the small particle pull-out and large particle cracking is concerned, when constructing the crack extension fracture model. Thereafter, the influence of particles’ volume fraction and matrix grain diameter on fracture strength is studied. The experimental data shows that the proposed strength prediction model is successful and can be generally applied.